Unity or Fragmentation in the Deep Blue: Choices in Institutional Design for Marine Biological Diversity in Areas Beyond National Jurisdiction - Berry, David S. (Frontiers in Marine Science, 2021)
Delegations are in the final stages of negotiating the proposed Agreement under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (BBNJ Agreement or Agreement). The Agreement will have tremendous scope. Geographically it covers all ocean areas beyond national jurisdiction, meaning approximately 60 percent of the earth’s surface. Substantively it deals with a range of complex topics necessary for the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction, including marine genetic resources, sharing of benefits, measures such as area-based management tools, including marine protected areas, environmental impact assessments and capacity-building and the transfer of marine technology. Existing scholarship primarily explores the substantive choices for the Agreement; little examines its proposed institutional structure. This article critically assesses the competing positions advanced during negotiations for the Agreement’s institutional structure – the ‘global’ and ‘regional’ positions – and reviews the middle, or ‘compromise’ position adopted by the draft text. It suggests that both global and regional actors will be necessary to conserve and sustainably use marine biological diversity of areas beyond national jurisdiction, and that some form of coordinating mechanism is required to allocate responsibility for particular tasks. Two principles are proposed for use in combination to provide a mechanism to help coordinate Agreement organs (global) and regional or sectoral bodies, namely, the principles of subsidiarity and cooperation. These principles are found in existing international and regional structures but are advanced here in dynamic forms, allowing for temporary or quasi-permanent allocation of competences, which can change or evolve over time. This position is also grounded in the international law of treaties and furthers dynamic views of regional and global ocean governance by offering practical coordinating principles that work with the existing Agreement text.